Profile variation of bla genes among non-lactose fermenting Gram-negative bacilli between clinical and environmental isolates of Dr. Soetomo Hospital, Surabaya, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Endraputra PN, Kuntaman K, Wasito EB, Shirakawa T, Raharjo D, Setyarini W. 2021. Profile variation of bla genes among non-lactose fermenting Gram negative bacilli between clinical and environmental isolates of Dr. Soetomo Hospital, Surabaya, Indonesia. Biodiversitas 22: 5047-5054. Carbapenem-resistant non-fermenter Gram-negative bacilli are notorious opportunistic pathogens in hospitalized patients and hospital environments. This study explored the carbapenemase gene among non-fermenter Gram-negative bacilli from hospital wastewater and clinical isolates in Dr. Soetomo Hospital, Surabaya, Indonesia. All samples were screened on MacConkey agar with meropenem 2 µg/ml and gene detected by Multiplex PCR. All samples were screened on MacConkey agar with meropenem 2 µg/ml and gene detected by Multiplex PCR. A total of 121 isolates consisted of 76 clinical (41 carbapenem-resistant Acinetobacter baumannii and 35 carbapenem-resistant Pseudomonas aeruginosa), 45 environmental isolates (6 carbapenem-resistant Pseudomonas aeruginosa and 32 carbapenem-resistant Pseudomonas spp.), and 7 screening samples (all CRPAs). Clinical isolates carbapenemase genes were identified, blaOXA-23-like 21 (28%), blaOXA-24-like 30 (39%), blaNDM-1 1 (1%), and blaIMP-1 6 (8%) while environmental isolates were blaOXA-23-like 5 (13%), blaOXA-24-like 4 (11%), blaOXA-48-like 2 (5%), blaNDM-1 13 (34%), blaVIM 12 (32%), and blaIMP-1 4 (11%). Rectal swab screening specimens presented blaOXA-23-like 3 (43%), blaOXA-24-like 3 (43%), and blaNDM-1 1 (14%). The carbapenemase gene pattern was different between clinical and environmental isolates. The blaOXA-23-like and blaOXA-24-like were most prevalent among in both clinical and wastewater, while blaVIM was mostly in wastewater. The presence of carbapenem-resistant non-fermenter Gram-negative bacilli carrying carbapenemase genes in hospital effluents indicated that the community river was seeded with an antimicrobial resistance gene.
Keywords: Acinetobacter baumannii; Pseudomonas aeruginosa; OXA; Carbapenemase gene; Wastewater